Use of long-acting reversible contraceptives in the UK from 2004 to 2010: Analysis using The Health Improvement Network Database. (December 2014) - Cea Soriano, Lucía; Wallander, Mari-Ann; Andersson, Susan; Filonenko, Anna; García Rodríguez, Luis Alberto
Abstract Objectives To determine the use of long-acting reversible contraceptives (LARCs) in the UK over the period 2004 to 2010, using the general practice database The Health Improvement Network (THIN). Methods Women in THIN, aged 18 to 44 years during 2004 to 2010, who had been registered with their general practitioner for at least five years, with a prescription history of at least one year were included. THIN was searched using the Read and MULTILEX codes for: copper intrauterine devices (Cu-IUDs), the levonorgestrel releasing-intrauterine system (LNG-IUS), progestogen-only implants, and progestogen-only injections. Results The prevalence of progestogen-only implant use rose from 0.5 to 3.4%, and that of the LNG-IUS from 3.1 to 5.2%. The annual incidence and prevalence of progestogen-only implant use increased for all age groups but was most marked in younger women, whereas the use of the LNG-IUS augmented with increasing age. For all women, there was a small decrease in the prevalence of use of Cu-IUDs (from 5.4 to 4.8%) and progestogen-only injections (from 3.6 to 3.2%). Conclusions Uptake of progestogen-only implants and the LNG-IUS increased over the period 2004 to 2010 in the UK, but LARC use in young women remains low.